(untitled) (LEARNing Landscapes, 2010)
The author describes her lifetime relationship with dance and how it has touched every aspect of her life—physical, spiritual and emotional. The control and discipline methods of teaching dance when she was a child were ill suited to her curiosity and creativity. This curiosity and her "soul’s yearning" have led her to explore dance as a source of knowledge, expression, exploration, communication and soul connection. As a teacher of dance, she describes how it is important to encourage her students to explore their relationship to themselves in dance. Lastly, she gives uplifting guidelines to inspire both teachers and readers.